2020
DOI: 10.2334/josnusd.19-0042
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene and oral status of institutionalized children with motor and intellectual disabilities

Abstract: The oral hygiene and oral status of children with severe disabilities with both nutritional and respiratory complications who were institutionalized at Karugamonoie (KNI), a facility for children with disabilities, were investigated in this study. Their oral hygiene management was solely dependent on caregivers and nurses at the institution. Thirty children (13 females, 17 males; average age, 7.6 years) who had a tracheotomy and feeding tube (gastrostomy, nasogastric, or jejunostomy feeding tube) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
7
0
3
Order By: Relevance
“…En relación a otro estudio de Ferreira et al las enfermedades periodontales se manifestaron con una rápida progresión incluso en los grupos de edad más jóvenes. (Bagattoni et al, 2016;Nasu et al, 2020;Ferreira et al, 2016) Un metanálisis de estudios de prevalencia realizado por Zhou et al en 2017 reveló altos índices de acumulación de placa, gingivitis y sangrado al sondaje para personas con discapacidad intelectual. (Zhou et al, 2017)…”
Section: Discussionunclassified
“…En relación a otro estudio de Ferreira et al las enfermedades periodontales se manifestaron con una rápida progresión incluso en los grupos de edad más jóvenes. (Bagattoni et al, 2016;Nasu et al, 2020;Ferreira et al, 2016) Un metanálisis de estudios de prevalencia realizado por Zhou et al en 2017 reveló altos índices de acumulación de placa, gingivitis y sangrado al sondaje para personas con discapacidad intelectual. (Zhou et al, 2017)…”
Section: Discussionunclassified
“…Another study with a similar conclusion reported that with professional caregivers, the quality of daily oral hygiene of children with motor and intellectual disabilities was very high even without on-site intervention by dental specialists. (Nasu et al, 2020)…”
Section: Discussionmentioning
confidence: 99%
“…Children with intellectual disabilities may have difficulty understanding and reporting their pain, so behavioral clues can be helpful in assessing the presence of pain (Alzahrani, 2019; Colak et al, 2013; Krekmanova et al, 2016; Narzisi et al, 2020; Nasu et al, 2020; Alaki and Bakry, 2012; Versloot et al 2006; Wyne, 2007). The Dental Discomfort Questionnaire (DDQ) is a dental pain assessment tool aimed at monitoring and scoring behaviors related to toothache and pain (discomfort while eating, sleep disorder and other pain-related behaviors) in children (Versloot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Oral health can adversely affect the QoL of adults and children, and their families. 10 The SOHI has been used to obtain information about the oral care habits and QoL of individuals varying in age, ethnicity, and sociocultural and health status 11 . In this study, the SOHI was higher in the HM group than the control group, despite similar sociocultural and economic conditions; the difference may have been related to treatment complications, such as mucositis, saliva volume and swallowing difficulties, along with poorer self-care in children with HM 12,13 .OHRQoL is an important public health issue with physical and psychological implications.…”
Section: Discussionmentioning
confidence: 99%